Evolution of interventional imaging in structural heart disease. (26th April 2023) - Agricola, Eustachio; Ingallina, Giacomo; Ancona, Francesco; Biondi, Federico; Margonato, Davide; Barki, Monica; Tavernese, Annamaria; Belli, Martina; Stella, Stefano
Abstract: Treatments for structural heart diseases (SHD) have been considerably evolved by the widespread of transcatheter approach in the last decades. The progression of transcatheter treatments for SHD was feasible due to the improvement of devices and the advances in imaging techniques. In this setting, the cardiovascular imaging is pivotal not only for the diagnosis but even for the treatment of SHD. With the aim of fulfilling these tasks, a multimodality imaging approach with new imaging tools for pre-procedural planning, intra-procedural guidance, and follow-up of SHD was developed. This review will describe the current state-of-the-art imaging techniques for the most common percutaneous interventions as well as the new imaging tools. The imaging approaches will be addressed describing the use in pre-procedural planning, intra-procedural guidance, and follow-up.